Prevalence of overactive bladder in China, Taiwan and South Korea: Results from a cross‐sectional, population‐based study1. Issue 1 (2nd October 2017) - Chuang, Yao‐Chi; Liu, Shih‐Ping; Lee, Kyu‐Sung; Liao, Limin; Wang, Jianye; Yoo, Tag Keun; Chu, Romeo; Sumarsono, Budiwan
Abstract : Objective: The aim of the present study was to determine the prevalence of overactive bladder (OAB) in individuals aged ≥40 years in China, Taiwan, and South Korea. Methods: The present cross‐sectional population‐representative Internet‐based study investigated OAB symptoms in men and women aged ≥40 years using the overactive bladder symptom score. Additional instruments included the International Index of Erectile Function (men only) and the Sexual Quality of Life – Female (women only) questionnaires, as well as Patient Perception of Bladder Condition (PPBC). Results: In all, 8284 individuals participated in the study. The prevalence of OAB was 20.8% overall (women 22.1%, men 19.5%) and increased significantly with age, from 10.8% in those aged 40–44 years to 27.9% in those aged >60 years ( P = .001). The presence of comorbid conditions (e.g. neurological disease, diabetes) was associated with a significantly increased prevalence of OAB. Increasing symptom severity was associated with significantly worsening patient perception of bladder condition responses. Just under half (48%) of those with no OAB had no lower urinary tract symptoms (LUTS), whereas 88% of those with severe symptoms had all 3 LUTS (International Continence Society definition) symptom categories (voiding, post‐micturition, and storage symptoms). Of those without OAB, 10% reported visiting healthcare professionals for urinary symptoms, compared with 64% of those with severe OAB symptoms ( P = .001). Increased symptom severity was significantly associated with lower sexual quality of life in both men and women. Conclusions: OAB symptoms were found to affect 1 in 5 individuals aged ≥40 years in China, Taiwan, and South Korea, becoming more common with increasing age. The results suggest that many more individuals with OAB could benefit by consulting healthcare professionals.